Psychological Well-Being Seen from Broken Home Students' Gratitude: a Phenomenological Study - Fausia Rahma Sa'adah; Ribut Purwaningrum; Naharus Surur (Indonesian Journal of Guidance and Counseling: Theory and Application, 2024)
This research aimed to (1) describe the meaning of gratitude in the lives of students from broken families, (2) their experiences of gratitude in the lives of students from broken families, (3) describe the meaning of psychological well-being in students from broken families, and (4) the essence of gratitude in students from broken families regarding the process of forming psychological well-being. To this end, a qualitative phenomenological study was applied. Participants were recruited using purposive sampling technique. The subjects in the research were broken families students. Data were collected through in-depth interview. The finding of this study showed that the conditions (1) four subjects were able to interpret gratitude in their lives, (2) all subjects were able to interpret the experience of gratitude in their lives, (3) four subjects were able to interpret psychological well-being in their lives which included self-acceptance; positive relationships with others; autonomy; mastery of the environment; life purpose, and personal growth, while one of the four subjects still has some difficulty in interpreting psychological well-being in the indicators of positive relationships with others and mastery of the environment, and (4) all subjects are able to interpret the essence of gratitude towards the process of developing psychological well-being. Penelitian ini bertujuan untuk (1) mendeskripsikan pemaknaan gratitude siswa broken home dalam kehidupannya, (2) mendeskripsikan pengalaman gratitude siswa broken home dalam kehidupannya, (3) mendeskripsikan pemaknaan psychological well-being pada siswa broken home dalam kehidupannya, dan (4) mendeskripsikan esensi gratitude siswa broken home terhadap proses pengembangan psychological well-being. Penelitian ini merupakan penelitian pendekatan kualitatif dengan metode studi fenomenologi dan desain penelitian fenomenologi hermeneutik. Teknik pengambilan sampel dilakukan dengan purposive sampling. Sampel penelitian terdiri dari empat dari populasi kurang lebih 25 siswa broken home. Subjek dalam penelitian ini adalah siswa broken home. Pengumpulan data dilakukan dengan wawancara mendalam. Hasil penelitian diperoleh dengan kondisi (1) empat subjek mampu memaknai gratitude dalam kehidupannya, (2) seluruh subjek mampu memaknai pengalaman gratitude dalam kehidupannya, (3) empat subjek mampu memaknai psychological well-being dalam kehidupannya yang meliputi penerimaan diri; hubungan positif dengan orang lain; otonomi; penguasaan lingkungan; tujuan hidup, dan pertumbuhan pribadi, sementara itu satu dari keempat subjek masih sedikit mengalami kesulitan dalam memaknai psychological well-being pada indikator hubungan positif dengan orang lain dan penguasaan lingkungan, dan (4) seluruh subjek mampu memaknai esensi gratitude terhadap proses pengembangan psychological well-being.